Making history at Sehonghong: Soai and the last Bushman occupants of his shelter - Mitchell, P. (Southern African Humanities, 2010)
Sehonghong Shelter is a site of considerable importance to southern African archaeology by reason of its rock paintings, a few of which were interpreted by a Bushman informant with knowledge of the art in 1879, and because of its long sequence of Later and Middle Stone Age assemblages with good organic preservation reaching back to 57000 years ago. This paper briefly summarises the history of archaeological research at the site, but focuses on its historical importance as a centre for the last generations of Bushmen to live in the Lesotho highlands. Historical accounts relating them to the site are discussed, the events surrounding the death there of the Bushman leader Soai described, and the implications of recently published oral histories indicating a post-Soai persistence of Bushman occupation considered. The paper ends by underlining the urgent necessity of further investigation of the site's remaining, and threatened, rock art and the importance of extending archaeological research to include the history of the local Basotho communities.